Analisa Korelasi Protokol Kesehatan Covid 19 Terhadap Keputusan Pembelian di Kedai Kopi Kiko, Jakarta - Hidayat, Candra; Haryono, Joko (Jurnal Ilmiah Pariwisata, 2021)
This study aims to determine the effect of health protocol correlation on purchasing decisions at Kiko Coffee Shop. The method of analysis in this study is simple regression analysis. The population in this study were all consumers of Kiko Coffee Shop. While the number of samples is 200 people. The sampling technique used is accidental sampling, where respondents meet directly with researchers, then fill out a google form. Health protocols have a significant effect on purchasing decisions at Kiko Coffee Shop because many consumers agree that Kiko Coffee Shop carries out health protocols so that consumers avoid the risk of being exposed to the Covid-19 virus. It is hoped that the Kiko Coffee Shop manager will continue to provide good service and continue to comply with the health protocol regulations that have been implemented so that consumers in general still feel comfortable and more satisfied when eating at Kiko Coffee Shop. Keywords: Covid 19, Health Protocol, Purchase Decision